Visual and Analytic Strategies in Geometry - Kospentaris, George; Vosniadou, Stella; Kazi, Smaragda; Thanou, Emiliana (Frontline Learning Research, 2016)
We argue that there is an increasing reliance on analytic strategies compared to visuo-spatial strategies, which is related to geometry expertise and not on individual differences in cognitive style. A Visual/Analytic Strategy Test (VAST) was developed to investigate the use of visuo-spatial and analytic strategies in geometry in 30 mathematics teachers and 134 11th grade students. Students’ performance in the VAST was also compared to performance in tests of visuo-spatial abilities, of abstract reasoning, and of geometrical knowledge. The results showed high performance of all the participants in the VAST items that could be solved by relying on visuo-spatial strategies. However, only the math teachers showed high performance in the VAST items that required the application of analytic geometrical strategies. There were high correlations between the students’ performance in the tests of visuo-spatial and abstract reasoning abilities and the VAST Analytic Strategies scale, but the contribution of these tests to the VAST analytic performance became statistically insignificant when geometrical knowledge was used as a mediating factor. The implications of this work for the learning and assessment of geometrical knowledge are discussed.